Analisis Yuridis Putusan Mahkamah Konstitusi Nomor 135/PUU-XXII/2024 terhadap Pemisahan Penyelenggaraan Pemilihan Umum di Indonesia - Miftahul Nur Azizah; Sarjiyati; Taufiq Yuli Purnama (Legal Standing : Jurnal Ilmu Hukum, 2026)
Elections in Indonesia continue to evolve to enhance the quality of democracy and administrative effectiveness. The Constitutional Court Decision Number 135/PUU-XXII/2024 establishes the separation of national and regional elections, driven by organizer fatigue and the risk of declining political representation quality due to simultaneous elections, and demands adjustments to Law Number 7 of 2017 and Law Number 6 of 2020. This research uses a normative juridical method with legislative, conceptual, and case approaches. The research results show that the separation of elections strengthens administrative effectiveness, the quality of political representation, and government stability, while simultaneously creating two different funding cycles between the national and regional levels. The main findings emphasize the need for regulatory harmonization, cross-level fiscal coordination, and transparent oversight mechanisms to maintain fiscal legitimacy and the quality of democracy, as well as to demonstrate the structural implications of constitutional decisions on the legal system and electoral budget management.